2013
DOI: 10.2460/ajvr.74.11.1428
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the cutaneus trunci muscle reflex in horses

Abstract: Findings of this study may have implications for assessment of nerve conduction velocities of the cutaneus trunci muscle reflex and may enhance understanding of the responses of horses to placement of tack or other equipment on skin over the cutaneus trunci muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In a study in horses, it was observed that the maximal contractile response of the PC to cutaneous stimuli was detected in areas where the cutaneous trunci muscle was thicker and the skin was more mobile (Essig et al. ).…”
Section: Does the Pc Form Part Of The Functional Skin Unit? Role In Dmentioning
confidence: 59%
“…In a study in horses, it was observed that the maximal contractile response of the PC to cutaneous stimuli was detected in areas where the cutaneous trunci muscle was thicker and the skin was more mobile (Essig et al. ).…”
Section: Does the Pc Form Part Of The Functional Skin Unit? Role In Dmentioning
confidence: 59%
“…Based on the findings of the non‐fatigable panniculus reflex in the horse (Essig et al. ), and the muscle being a part of the lateral myofascial kinetic line (Elbrønd & Schultz, ), and the recent morphological and topographical findings, we suggest that the muscle takes part in stabilization of the trunk at fast speed such as trot and canter.…”
Section: Discussionmentioning
confidence: 70%
“…; Essig et al. ). Based on the findings of the non‐fatigable panniculus reflex in the horse (Essig et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The m. cutaneous trunci attaches between the skin and fascia, covering the thoracic walls and unites with mm. pectorals, latissimus dorsi and teres major through fascial bands [49,50]. As m. cutaneous trunci responses to tactile stimulation of the skin [49] kinesiotape may be a method to consider when trying to activate the abdominal muscles.…”
Section: Discussionmentioning
confidence: 99%